Effect of enamel protective agents on shear bond strength of orthodontic brackets - Montasser, Mona A (Springer Berlin Heidelberg, 2014)
BACKGROUND: This paper aimed to study the effect of two enamel protective agents on the shear bond strength (SBS) of orthodontic brackets bonded with conventional and self-etching primer (SEP) adhesive systems. METHODS: The two protective agents used were resin infiltrate (ICON) and Clinpro; the two adhesive systems used were self-etching primer system (Transbond Plus Self Etching Primer + Transbond XT adhesive) and a conventional adhesive system (37% phosphoric acid etch + Transbond XT primer + Transbond XT adhesive ). Sixty premolars divided into three major groups and six subgroups were included. The shear bond strength was tested 72 h after bracket bonding. Adhesive remnant index scores (ARI) were assessed. Statistical analysis consisted of a one-way ANOVA for the SBS and Kruskal-Wallis test followed by Mann-Whitney test for the ARI scores. RESULTS: In the control group, the mean SBS when using the conventional adhesive was 21.1 ± 7.5 MPa while when using SEP was 20.2 ± 4.0 MPa. When ICON was used with the conventional adhesive system, the SBS was 20.2 ± 5.6 MPa while with SEP was 17.6 ± 4.1 MPa. When Clinpro was used with the conventional adhesive system, the SBS was 24.3 ± 7.6 MPa while with SEP was 11.2 ± 3.5 MPa. Significant differences in the shear bond strength of the different groups (P = .000) was found as well as in the ARI scores distribution (P = .000). CONCLUSION: The type of the adhesive system used to bond the orthodontic brackets, either conventional or self-etching primer, influenced the SBS, while the enamel protective material influenced the adhesive remnant on the enamel surface after debonding.